Genesis n° 48 (2019), « Écritures Jeunesse » (edited by Christine Collière-Whiteside and Karine Meshoub-Manière) (Prassi Ecdotiche della Modernità Letteraria, 2020)
This review is dedicated to «Genesis» 48 (2019). «Genesis» is a six-monthly magazine in French, promoted by the Institut des textes et manuscrits modernes (ITEM) in Paris, the center of studies and reflections on genetic criticism. This number, entitled "Écritures Jeunesse" and edited by Christine Collière-Whiteside and Karine Meshoub-Manière, is available online at the following address: https://journals.openedition.org/genesis/1722